Political Influence and Third Sector’s Umbrella Organizations. A first Comparision between Italy and Spain - Pedercini, Claudia (Italian Sociological Review, 2015)
The paper focuses on the analysis of the relationship between third sector and state and on the demanding nature of this relationship, with the objective of analyzing the components, requirements and thoughts behind it. In particular, the specific topic refers to the deepening of political influence exerted by the Spanish and Italian umbrella organizations of the third sector engaged in forms of political influence. The collected information has been analyzed with a specific software that uses Qualitative Comparative Analysis (QCA).